Jual Beli Pakaian Bekas (Thrift) Perspektif Ekonomi Islam: Studi Kasus Di Raskin Second Store Gresik - Tamam, Ahmad Badrut (Al-Musthofa: Journal of Sharia Economics, 2024)
This research describes the mechanism for buying and selling used clothes at the Raskin Second Store and how the buying and selling of used clothes is done from an Islamic Economics perspective. The results of this research show that the mechanism for buying and selling used clothes includes: stock procurement, sorting process, cleaning, photographing, giving away. prices, displays and buying and selling transactions with customers. In buying and selling used clothes, Raskin Second Store has implemented several Islamic economic principles, namely monotheism, morals, justice, balance and freedom.